Grounds and preparations for the main thesis of "Veritatis Splendor" - Finnis, John (Studia Philosophiae Christianae, 2017)
Having set out in some detail the central teaching of the encyclical “Veritatis Splendor” – on exceptional moral norms – this paper outlines some of the preparatory work done by the International Theological Commission in a document which, though adopted with virtual unanimity by the Commission, remains unpublished because it so closely preceded the encyclical. In a third section, the paper recalls relevant teachings of Vatican II and of the Holy See that the ITC document recalled in support of its thesis. The fourth section of the paper offers some further reflections on the encyclical, its foundations and its significance.